2021
DOI: 10.51201/jusst/21/09686
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive review on Dichrostachys cinerea

Abstract: For a very long time, the medical plants have been used worldwide to treat human diseases and it serves as a safe source of drugs to cure several diseases and conditions through complementary medicine system. It is a native plant of Indian subcontinent, Africa and North Australia and is known to have significant pharmacological activities. The wide range of pharmacological activities of D.cinerea are due to the presence of different groups of active biological compounds present in it. Traditionally, D.cinerea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Our previous studies also indicated the analgesic effect of DC fruits water extract, but in a different model of pain (induced by acetic acid) and acute inflammation (induced by carrageenan) that the one presented in this study (induced by CFA) [ 12 ]. Dychrostachis cinerea analgesic effect was also reported in the literature for DC leaf, roots, or bark extracts in different acute inflammatory pain models [ 8 , 42 ], but to our knowledge, there are no references regarding the analgesic effect in chronic pain models.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our previous studies also indicated the analgesic effect of DC fruits water extract, but in a different model of pain (induced by acetic acid) and acute inflammation (induced by carrageenan) that the one presented in this study (induced by CFA) [ 12 ]. Dychrostachis cinerea analgesic effect was also reported in the literature for DC leaf, roots, or bark extracts in different acute inflammatory pain models [ 8 , 42 ], but to our knowledge, there are no references regarding the analgesic effect in chronic pain models.…”
Section: Discussionmentioning
confidence: 93%
“…It is widespread in Africa and India, and is considered an invasive species in the Caribbean. Dichrostachys cinerea ’s bark, roots, and fruit pods are used in traditional medicine as remedies against common health problems such as fever, pain, and diarrhea, but it also has laxative properties [ 8 ]. It is also used in some populations to prevent sexually transmitted diseases [ 9 , 10 ], for cicatrizing effects [ 11 , 12 ], or as an anti-inflammatory agent [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This assertion validates the indigenous knowledge of villagers. Equally, as echoed by the villagers in Mafarana, while the plant has detrimental effects to the environment, grasses, and other surrounding plants, it has proven to also have beneficial uses (i.e., medicinal, animal feed, and firewood, as scientifically corroborated by numerous scholars [36][37][38]). This observation validates the space and need for co-existence of these knowledge systems within society.…”
Section: Community Perceptions Toward Bush Encroachmentmentioning
confidence: 90%